Analysis of anxiety and work stress in primary health care professionals (Research, Society and Development, 2021)
Objective: To analyze the level of anxiety and work stress in workers of the Basic Health Units of Caxias-MA. Methodology: This is an analytical, cross-sectional study with a quantitative approach. Seventy-one (71) workers answered the sociodemographic and occupational questionnaire, the anxiety scales, Trait-State Anxiety Inventory (STAI) and stress, Stress at Work Scale (TSE). The data from the methodological instruments were tabulated using the Office Excel version 2013 program, a database was created, and later, analyzed electronically by the SPSS 22.0 program for Windows. Results and discussion: The predominance of the average level of anxiety and stressful factors was evidenced, with the vigilant ones being the most anxious and stressed. Workers with more than one occupation have higher levels of anxiety. Regarding Neuromusculoskeletal Disorder (DNME), there is a predominance among the watchmen, however in all professions the existence of this disorder was observed, except receptionist. The results show that of the 21 workers with another occupation, 11 have DNME. Conclusion: It is necessary to develop a more careful look at the physical and mental health of workers such as strengthening social support at work, the importance of ergonomics, moments of team interaction, qualified listening, in addition to activities that can enrich and reorganize the process and workflow, together with the advice of management and supervisory bodies. Due to research limitations, the emergence of other studies on care for workers' health is of great importance.